1997
DOI: 10.1046/j.1365-2958.1997.3131693.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Aspergillus nidulans treA gene encoding an acid trehalase required for growth on trehalose

Abstract: SummaryAspergillus nidulans conidiospores contain high levels of the non-reducing disaccharide trehalose. We show that upon induction of conidiospore germination, the trehalose pool is rapidly degraded and a glycerol pool is transiently accumulated. A trehalase with an acidic pH optimum was purified from conidiospores. Characterization of the treA gene encoding this trehalase shows that it is homologous to Saccharomyces cerevisiae vacuolar acid trehalase, the product of the ATH1 gene, and to two related protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 47 publications
5
95
0
Order By: Relevance
“…The acid trehalase is extracellular in many other fungi (9,10,24,29) and in prokaryotes (6). Ath1p may be localized in vacuoles in S. cerevisiae (1,12,25).…”
Section: Trehalose [␣-D-glucopyranosyl-(1-1)-␣-d-glucopyranoside] Is mentioning
confidence: 99%
See 1 more Smart Citation
“…The acid trehalase is extracellular in many other fungi (9,10,24,29) and in prokaryotes (6). Ath1p may be localized in vacuoles in S. cerevisiae (1,12,25).…”
Section: Trehalose [␣-D-glucopyranosyl-(1-1)-␣-d-glucopyranoside] Is mentioning
confidence: 99%
“…While Nwaka and coworkers (36) suggested that trehalose may reach the vacuole by simple endocytosis, Malluta et al (30) proposed that the disaccharide could be taken up by Agt1p. However, to be effective, this model implies the protection of internalized trehalose against neutral trehalase and the existence of two additional transporter activities by which trehalose enters the vacuole to be degraded by Ath1p and the subsequent exit of glucose from this compartment.The acid trehalase is extracellular in many other fungi (9,10,24,29) and in prokaryotes (6). Ath1p may be localized in vacuoles in S. cerevisiae (1,12,25).…”
mentioning
confidence: 99%
“…It could therefore be suggested that this enzyme is active as a monomer. This is in contrast to other acid trehalases that are often active as dimers or multimers (Sumida et al, 1989 ;Zimmerman et al, 1990 ;Kadowaki et al, 1996 ;d'Enfert & Fontaine, 1997). Because the acid trehalase binds to concanavalin A, it is probably a glycosylated protein.…”
Section: mentioning
confidence: 99%
“…The concentrations of trehalose, mannitol, arabitol, and glycerol in the resting and germinating conidia were analyzed as described previously (23). Briefly, 1-week-old conidia (produced in 2% malt extract agar medium) were incubated in Sabouraud (SAB) liquid medium for 0 h, 3 h, and 6 h at 37°C in shake flasks at 300 rpm.…”
Section: Methodsmentioning
confidence: 99%